Silver Diamine Fluoride In Dentistry: A Review Of Clinical Applications And Future Prospects (Global Journal of Medical Research, 2024)
This review critically examines the utilization of Silver Diamine Fluoride SDF in modern dentistry focusing on its clinical applications limitations and prospective areas for further investigation Positioned as an alternative to conventional caries management strategies particularly in addressing the prevalent issue of childhood caries SDF has garnered attention for its potential to minimize patient anxiety associated with traditional dental procedures Drawing insights from studies conducted in various regions including Japan London Cuba Brazil and Nepal the article highlights the substantial fficacyof SDF in arresting both cavitated and incipient cariouslesions Noteworthy is its role as a viable option when restorative treatment for primary teeth is impractical The review emphasizes SDF s unique application in managing early childhood caries and underscores its significance in preserving the structural integrity of deciduous teeth and supporting jawbone development
Keywords: silver diamine fluoride; dental caries; atraumatic restorative techniques; dentin hypersensitivity; caries arrest; fluoride